Problematic caregiving activities among family carers of older adults with disabilities. (1st November 2021) - Atoyebi, Oladele; Beaudoin, Maude; Routhier, François; Auger, Claudine; Demers, Louise; Wister, Andrew; Plante, Michelle; Mortenson, W. Ben
Abstract : Family carers of older adults with disability often both experience stress that may affect their ability to provide care, and find some caregiving activities differentially challenging. The objectives of this research are to identify the caregiving activities that are most problematic to carers and to explore the reasons why carers found these activities challenging. Participants were past or current carers aged 19 years and older. Using an explanatory sequential mixed-methods approach, data were collected through a survey and open-ended interviews. Thematic analysis revealed that an activity was likely to be more problematic if it had to be coordinated with other caregiving needs or where a care recipient's disability was severe.